PENERAPAN PEMBERIAN MINYAK ZAITUN (OLIVE OIL) UNTUK MENGURANGI KERUSAKAN INTEGRITAS KULIT PADA ANAK USIA SEKOLAH (6 TAHUN) DENGAN THALASEMIA DI RSUD KARAWANG - Yuli Erlina,; Grace Evelyn,; Nurmala Dewi Putri, (Journal of Innovation Research and Knowledge, 2024)
Thalassemia is a congenital disease caused by red platelet anomalies. Thalassemia sufferers will experience blood deficiency because red platelets do not contain enough hemoglobin,And it will rupture without any problems and cause blood deficiency, thalassemia disease. Thalassemia patients have the same problem, namely dry skin that causes clinical manifestations so that problems arise with damage to skin integrity. The number of thalassemia sufferers is estimated to reach 156.74 million people or around 20% of the total world population. At the Karawang Regional Hospital, to be precise, in the thalassemia polyclinic in the last 6 months, the number of patients was 160 child cases or around 69.57% and the average patient was school age children. Management of damage to skin integrity can be done by administering olive oil. The purpose of giving olive oil is to reduce damage to skin integrity. The subject used was 1 thalassemia pediatric patient with impaired skin integrity. The application of olive oil is applied all over the body for 2 consecutive days with a frequency of 3 times a day, and with an adequate dose (1 - 2 teaspoons or 5 - 10 ml). The results of the application showed an increase in skin integrity with an initial score of 15 with a percentage of 4.5% and a final score of 21 or around 6.3% and an increase with a score of 6 of around 1.8%.